Understanding Traditional Chinese Medicine to strengthen conservation outcomes. Issue 1 (25th November 2020) - Cheung, Hubert; Doughty, Hunter; Hinsley, Amy; Hsu, Elisabeth; Lee, Tien Ming; Milner‐Gulland, E. J.; Possingham, Hugh P.; Biggs, Duan
Abstract: Numerous treatments in Traditional Chinese Medicine (TCM) involve the use of wildlife products, including some that utilize ingredients derived from endangered flora and fauna. Demand for such endangered wildlife products in TCM can threaten the survival of species and pose serious challenges for conservation. Chinese medical practice is embedded in the cultural fabric of many societies in East and Southeast Asia, and remains an integral part of everyday life and knowledge. It is grounded in principles and theories that have grown over hundreds of years and differ substantially from those of mainstream allopathic biomedicine. In order to address the threats posed by the medicinal consumption of endangered wildlife, conservation scientists and practitioners will benefit from a basic understanding of TCM. Such knowledge will enable conservationists to craft culturally nuanced solutions and to engage constructively with TCM stakeholders. However, conservationists typically lack familiarity with TCM as the incompatibility of many TCM concepts with those of the biomedical sciences poses a barrier to understanding. In this paper, we examine the core theories and practices of TCM in order to make TCM more accessible to conservation scientists and practitioners. A better understanding of TCM will enable conservationists to deliver more effective and lasting conservation outcomes. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 抽象: 繁體中文標題 : 深入了解中醫藥學以加強保育項目的有效性 繁體中文摘要 : 中醫藥的治療方法會使用到來自瀕危動植物的產品。此類產品的需求可能會威脅瀕危動植物的存續, 為生態保育帶來挑戰。中醫藥文化在亞洲多地已經根深蒂固, 成為日常和知識體系中不可或缺的一部分。中醫藥學的原理和理論源遠流長, 建基於幾千年的發展, 跟主流西醫藥學有很大分別。其概念認知差異導致保育者對中醫藥的理解產生歧義。保育者需要了解中醫藥學對瀕危動植物的文化需求, 以制訂更有效的保育方案。本文考察了中醫藥學的核心理論和實踐方法, 使保育項目產生更持久的影響力。 简化中文标题 : 深入了解中医药学以加强保育项目的有效性 简化中文摘要 : 中医药的治疗方法会使用到来自濒危动植物的产品。此类产品的需求可能会威胁濒危动植物的存续, 为生态保育带来挑战。中医药文化在亚洲多地已经根深蒂固, 成为日常和知识体系中不可或缺的一部分。中医药学的原理和理论源远流长, 建基于几千年的发展, 跟主流西医药学有很大分别。其概念认知差异导致保育者对中医药的理解产生歧义。保育者需要了解中医药学对濒危动植物的文化需求, 以制订更有效的保育方案。本文考察了中医药学的核心理论和实践方法, 使保育项目产生更持久的影响力。